Does Background Matter? The Transmission of Human Capital from a Planned to a Market Economy - Ira N. Gang; Robert C. Stuart (Rutgers University, Department of Economics, 1999)
We analyze the early U.S. economic achievement of former Soviet citizens entering the United States during the period 1979 through 1985. Using the Soviet Interview project (SIP) data, we identify components of human capital acquired in the former Soviet Union (FSU), relating these to labor force participation and income outcomes in the United States. FSU education, experience and industry variables have important, variable and differing impacts upon both participation and income, and that such outcomes differ for males and females. FSU immigrants income is below U.S. income. Differing rates of return to characteristics, not the endowments themselves, are responsible for observed differentials.
Keywords: J24; J31; J61; 330; Comparative systems; Human capital; Immigration; Wage differentials